ANALISIS LAMANYA PIDANA TERHADAP PELAKU PERSETUBUHAN ANAK YANG MEMILIKI HUBUNGAN KELUARGA: Analysis of the Length of Criminal Against the Actor of Intercourse Children Who Have Family Relations - Usman, Nurfaizi; Wangga, Maria Silvya Elizabeth (AMICUS CURIAE, 2024)
Intercourse with minors who have family relations has been terminated by the West Jakarta District Court Number: 1596/Pid.Sus/2020/PN Jkt.Brt where the perpetrator is the victim's uncle who forcibly commits intercourse with minors, in this case his nephew. The provisions for the burden of punishment for perpetrators of intercourse with children who have family relations are burdened with 1/3 (one third) of the length of the prison sentence for the perpetrator, which is 7 (seven) years. There are 2 (two) main issues that are raised. The main issues that are raised are what are the provisions for the duration of the crime for perpetrators of intercourse with children who have family relations and how are the provisions for aggravating crimes for perpetrators of intercourse with children who have family relations. The research was conducted normatively with the nature of descriptive analytical research and drawing conclusions using deductive logic methods. The results of the research show that the length of time the perpetrator of sexual intercourse with a child who has a family relationship is sentenced to 5 (five) years in prison under Article 81 (2) juncto Article 76D of the Child Protection Act. The penalty for the perpetrator is increased by 1/3 (one third) to 7 (seven) years, the maximum penalty under Article 81 (3) must be imposed on the perpetrator. It is hoped that the judge who decides will be able to renew and improve the provisions on the length of his sentence based on the Child Protection Law, and the government hopes to establish new criminal guidelines for the Child Protection Act.